QUARANTINE VLOGS: DIGITAL AFFECTIVE LABOR AND SELF-GOVERNANCE DURING COVID-19 - Yalın, Alkım (AoIR Selected Papers of Internet Research, 2021)
This research explores how did influencers incorporate the Covid-19 pandemic into their regular content production on YouTube by specifically examining the recent genre of "quarantine vlog," which emerged in concurrence with global lockdowns. I adopt a grounded theory approach to analyze the YouTube transcriptions of purposefully selected 9 quarantine vlogs filmed by women influencers during the early months of the pandemic, along with 250 user comments. My analysis shows that quarantine vlogs are significantly different than ordinary vlogs. I draw on existing research on influencer cultures to explain this dissimilarity as a tension between influencers' struggle to form an intimacy with the viewers - which can have a soothing effect in a moment of a crisis - and the use of vlogs as a neoliberal device in order to preserve their aspirational image. I demonstrate that quarantine vlogs reveal that influencers are no longer able to perform an aspirational ideal in their videos without first engaging with the mental stress, anxiety, confusion, and loneliness brought by COVID-19 or apologizing for their relative privilege and demonstrating sympathy towards their followers who are in hardship. At the same time, to preserve their aspirational persona, they reframe the pandemic moment as an opportunity for productivity and self-growth. As a result, influencers carry out substantial affective labor and engage in a delicate self-governance to preserve their relevance and online visibility during a global moment of crisis.